PERBANYAKAN Trichoderma harzianum PADA MEDIA BERBASIS ELA SAGU - A. Marthin Kalay; Abraham Talahaturuson (Jurnal Agroekoteknologi, 2014)
Trichoderma harzianum has been widely known as biological control agents of plant diseases. To obtain inoculum in large quantities waste agricultural products could be used as media. Ela sago is solid wastes originated from sago processing, contains C-organic, nitrogen, phosphorus, potassium, calcium, magnesium, as well as crude protein, fat, crude fiber, ash, cellulose, hemicellulose, lignin, and silica. The objective of this laboatory experiment was to determina the capacity of ela sagu in combination with rice bran and husks as T. harzianum inoculum production. The research was conducted in laboratorium Nemathology, Plant Pathology Agriculture Faculty of Pattimura University. The experiment was conducted from March to April 2014. The medium testedin this experiment were ela sago, ela sago + husk, ela sago + bran, ela sago + husk + bran, husk, bran, husk + bran, and corn. The experiment was set up by using a completely randomized design, replicated three times. The experimental results showed that the number of conidiumon mixed media ela sago + bran and ela sago + bran + husk reached up to 1011 per g media and significantly greater than that of ela sago, elasago + husk, Husk + bran, husk, bran, and corn media.